2008
DOI: 10.1016/j.brainresbull.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of a geometric rule or absolute vectors: Landmark use by Clark's nutcrackers (Nucifraga columbiana)

Abstract: Clark's nutcrackers (Nucifraga columbiana) were trained to search for a hidden goal located in the center of a four-landmark array. Upon completion of training, the nutcrackers were presented with tests that expanded the landmark array in the east-west direction, north-south direction and in both directions simultaneously. Although the birds learned to search accurately at the center of the landmark array during training, this search pattern did not transfer to the expansion tests. The nutcrackers searched at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…By contrast, in the absence of any featural polarizing cue, chicks efficiently reorient themselves on the basis of the macroscopic layout of surfaces provided by a small rectangular enclosure (Vallortigara et al, 1990). Results with chicks in the rectangular array apparently are in contrast to the hypothesis that avian species rely on vector strategies to reorient by landmarks [pigeons (Cheng, 1990;Spetch et al, 1992;Spetch et al, 1996;Spetch et al, 1997) (see also Cheng et al, 2006), Clark's nutcrackers (Kelly et al, 2008)]. If chicks were able to encode absolute distances and directions from the rewarded site and the surrounding cues, they would be expected to reorient by geometry in the rectangular array of landmarks.…”
Section: Introductionmentioning
confidence: 93%
“…By contrast, in the absence of any featural polarizing cue, chicks efficiently reorient themselves on the basis of the macroscopic layout of surfaces provided by a small rectangular enclosure (Vallortigara et al, 1990). Results with chicks in the rectangular array apparently are in contrast to the hypothesis that avian species rely on vector strategies to reorient by landmarks [pigeons (Cheng, 1990;Spetch et al, 1992;Spetch et al, 1996;Spetch et al, 1997) (see also Cheng et al, 2006), Clark's nutcrackers (Kelly et al, 2008)]. If chicks were able to encode absolute distances and directions from the rewarded site and the surrounding cues, they would be expected to reorient by geometry in the rectangular array of landmarks.…”
Section: Introductionmentioning
confidence: 93%
“…B ϭ beacon search; M ϭ middle rule; V ϭ vector search. tances) may have a crucial influence on which strategy is preferentially used (Kelly et al, 2008).…”
mentioning
confidence: 99%
“…Comparable findings have been obtained in an array of freestanding objects of a similar geometric shape (Kelly et al 2008). Monocular test revealed that both the left and the right eye mediate the activation of a local searching strategy in pigeons when the position of the goal is defined by the shape of the arena (Kelly et al 2008). There is no evidence of separate contribution between the left and the right hemisphere for relational spatial learning in pigeons.…”
Section: Lateralization Of Familiar Landmark-based Navigationmentioning
confidence: 50%
“…Pigeons trained to locate a food reward at the centre of an arena tend to focus their searches at approximately the same distance from the walls in an expansion test (Wilzeck et al 2009). Comparable findings have been obtained in an array of freestanding objects of a similar geometric shape (Kelly et al 2008). Monocular test revealed that both the left and the right eye mediate the activation of a local searching strategy in pigeons when the position of the goal is defined by the shape of the arena (Kelly et al 2008).…”
Section: Lateralization Of Familiar Landmark-based Navigationmentioning
confidence: 56%